Examination of influenza specific T cell responses after influenza virus challenge in individuals vaccinated with MVA-NP+M1 vaccine. - Timothy J Powell; Yanchun Peng; Tamara K Berthoud; Marie-Eve Blais; Patrick J Lillie; Adrian V S Hill; Sarah L Rowland-Jones; Andrew J McMichael; Sarah C Gilbert; Tao Dong (PLoS ONE)
Current influenza vaccines stimulate neutralising antibody to the haemagglutinin antigen but as there is antigenic drift in HA it is difficult to prepare a vaccine in advance against an emergent strain. A potential strategy is to induce CD8(+) and CD4(+) T cells that recognize epitopes within internal proteins that are less subject to antigenic drift. Augmenting humoral responses to HA with T cell responses to more conserved antigens may result in a more broadly protective vaccine. In this study, we evaluate the quality of influenza specific T cell responses in a clinical trial using MVA-NP+M1 vaccination followed by influenza virus challenge. In vaccinated volunteers, the expression of Granzyme A, Perforin and CD57 on influenza HLA A*02 M158-66 antigen specific cells was higher than non-vaccinated volunteers before and after challenge despite a similar frequency of antigen specific cells. BCL2 expression was lower in vaccinated volunteers. These data indicate that antigen specific T cells are a useful additional measure for use in human vaccination or immunization studies.